Crop production of the North Kazakhstan region as the basis of the agricultural cluster and ensuring food security of the population - Chistyakova, G.N.; Salykbayeva, G.M.; Dosmakhov, S.M.; Kozhakhmetova, L.T.; Kulmaganbetova, А.О. (Fundamental and Experimental Biology, 2022)
The scientific article discusses the features of the development and location of crop production in the North Kazakhstan region, which is the main key branch of the agricultural cluster of the region and the basis for en-suring food security of the population. The purposeof the work is to identify the current state and trends in the development of the industry. Applying the economic and geographical method of research, the authors of the article conclude that ensuring food security both for the population of a particular region and for the coun-try as a whole is possible by solving two main problems. This is a transition to an innovative way of devel-opment and acceleration of import products substitution. All this poses an important strategic task for the agro-industrial complex to increase the efficiency of production in agriculture, including crop production. The North Kazakhstan region, being one of the leading regions in the structure of agricultural production of the Republic of Kazakhstan, is the most interesting froma scientific point of view for studying the tasks set.